2016
DOI: 10.1371/journal.pone.0162108
|View full text |Cite
|
Sign up to set email alerts
|

Educational Level, Anticoagulation Quality, and Clinical Outcomes in Elderly Patients with Acute Venous Thromboembolism: A Prospective Cohort Study

Abstract: Whether the level of education is associated with anticoagulation quality and clinical outcomes in patients with acute venous thromboembolism (VTE) is uncertain. We thus aimed to investigate the association between educational level and anticoagulation quality and clinical outcomes in elderly patients with acute VTE. We studied 817 patients aged ≥65 years with acute VTE from a Swiss prospective multicenter cohort study (09/2009-12/2013). We defined three educational levels: 1) less than high school, 2) high sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
2
0
1
Order By: Relevance
“…Of the 26 included studies, 12,26–49 14 were RCTs and 12 were prospective cohort studies with a total of 15 603 patients with a first unprovoked or weakly provoked VTE who, after having completed at least 3 months of initial anticoagulant treatment, received extended anticoagulation (Table 1). The duration of initial anticoagulant treatment was exclusively 3 months in 12 studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 26 included studies, 12,26–49 14 were RCTs and 12 were prospective cohort studies with a total of 15 603 patients with a first unprovoked or weakly provoked VTE who, after having completed at least 3 months of initial anticoagulant treatment, received extended anticoagulation (Table 1). The duration of initial anticoagulant treatment was exclusively 3 months in 12 studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…play roles in reaching the effective TTR levels. It has been demonstrated that the educational level of patients play roles in the efficacy and safety of warfarin ( 23 - 26 ). In the present study, nearly half of the patients were primary school-graduates, and no significant differences were detected between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Entretando, o nível de escolaridade menor não esteve associado com a ocorrência dos desfechos clínicos. Estes resultados são semelhantes ao observado por Hofmann e colaboradores que encontraram uma incidência cumulativa de 3 anos de TEV recorrente e sangramento maior, sem diferença entre as três categorias educacionais nos pacientes em uso de anticoagulantes 112 .…”
Section: Análise Dos Pacientes Que Realizaram Troca De Femprocumona P...unclassified